Diversity of Ralstonia pseudosolanacearum, the causal agent of bacterial wilt on Eucalyptus pellita in Indonesia - Bayo Alhusaeri Siregar; Giyanto Giyanto; Sri Hendrastuti Hidayat; Iskandar Zulkarnain Siregar; Budi Tjahjono (Society for Indonesian Biodiversity, 2021)
Abstract. Siregar BA, Giyanto, Hidayat SH, Siregar IZ, Tjahjono B. 2021. Diversity of Ralstonia pseudosolanacearum, the causal agent of bacterial wilt on Eucalyptus pellita in Indonesia. Biodiversitas 22: 2538-2545. The Ralstonia species complex was initially classified into five races and five biovars but the classification could not accommodate the isolates' phylogenetic history or geographic origins. A phylotype and sequevar system is based on the geographic distribution and characteristics of endoglucanase (egl) and hypersensitive response and pathogenicity (hrp) gene sequences. This study aims to describe pathogen diversity of the causal agent of bacterial wilt on Eucalyptus pellita F. Muell. Pathogens were isolated from wilting seedlings and trees in several Eucalyptus plantations. The phenotypic diversity analysis included biovar, exopolysaccharide quantification and virulence tests, while genotypic diversity included phylotypes and sequevar determination based on egl gene sequences. A total of 35 strains were isolated from the field and nurseries of Eucalyptus in various locations. All isolates were confirmed as Ralstonia species complex based on morphological characteristics and molecular studies using species-specific primers. These isolates were dominantly classified as biovar 3 and 4 and had a high variation on virulence and EPS production. Based on the egl sequence's alignment, 29 strains of Phylotype I are grouped into four sequevar references (sequevars 14, 17, 18, 30) and new a sequevar 58. This study shows that strains of R. pseudosolanacearum causing bacterial wilt on E. pellita in Indonesia have high phenotypic and genotypic diversities.